PEMANFAATAN SISTEM INFORMASI AKUNTANSI PADA UMKM DI KOTA SEMARANG - Nugraha, Nyata; Budiyono, Iwan; Nurhayati, Ida; Arumsari, Vita (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2023)
This study aims to analyze the implementation and use of accounting information systems in Micro, Small and Medium Enterprises (SMEs) in the service and trade sector in Semarang City. The population of this research is SMEs in the service and trade sector in the city of Semarang. The sampling technique in this study used the stratified random sampling method. The number of samples in this study were 104 SMEs. This study uses descriptive analysis to analyze the results of the survey questionnaire. It was found that the problem with the Accounting Information System (AIS) in SMEs starts from limited capital for SMEs so that they are unable to pay employees in the accounting department, or for reasons of efficiency. So that the bookkeeping or accounting records of the company are the owners themselves. Meanwhile, SMEs owners do not have sufficient knowledge of accounting. Limited capital and lack of knowledge about accounting, causes SMEs not to use the Accounting Information System (AIS) in recording their business transactions. This is what causes SMEs not to compile financial reports, both in the form of Income Statements and Statements of Financial Position. This problem is the basis for the preparation of accounting applications for SMEs.